Propuesta de un manual de buenas prácticas de manufactura para la mejora técnica en el taller de procesos cárnicos - ESPAM-MFL - Solórzano Sánchez, Mayra Elizabeth (2013)
Carrying out this investigation was necessary to get information for more precise ways to meet the primary goal, taking into account important mechanisms to improve the functioning of various areas of the Process Meat Workshop in the PolytechnicAgricultural University of Manabí Manuel Felix Lopez according to criteria already set as references. A performance diagnose of the elements identified currently characterizing of the workshop by observation and interview, including a SWOT analysis by matrix showing the internal and external behavior, stating the strengths cover the weaknesses by 3.50 according to the indicator and opportunities over threats by 3.29, finding the institution is strategic offensive, later determined the organization flow chart that will organized every function, and then identify the processes used in the meat products and application of different quality standard. Having identified the problem a manual for Good Manufacturing Practices was elaborated based on the components that were considered in the plant taking into account the development of index cards that allow to control in terms of compliance with this tool, assuring a technical improvement within the workshop areas where different processes and activities are performed supported under letter No. 003-13 TPC accepted by Mr. Tobias Ramon Rivadeneira García.